Simulating the dynamics of lipid droplets in adipocyte differentiation. (January 2017) - Boschi, Federico; Rizzatti, Vanni; Zamboni, Mauro; Sbarbati, Andrea
Highlights: The interaction between cellular organelles, like lipid droplets, can be numerically simulated. Many interactions can be simulated in a very brief computational time. Many different processes can be explored. All the needed information, both theoretical and experimental, are provided in order to repeat the procedure. Abstract: Background: Lipid droplets are cellular organelles that regulate the storage and hydrolysis of neutral lipids. The dynamic of lipid droplets (LDs), during the differentiation process from fibroblast-like cells into adipocyte, is strictly related to the lipid storage in cells. The number and size of the LDs depends on the lipidic or lipolytic stimulations to which the cells are exposed. Method: Here, we propose a computational approach to study the processes regulating the LDs' number and growth/reduction in size using Monte Carlo simulations. The number and size of LDs are measured before and after experimental treatment in 3T3-L1 cell cultures. The algorithms simulating the evolution from basal to differentiate (lipidic or lipolytic) conditions are here detailed step by step. The algorithms can mimic thousand interacting events between LDs or squeezing/enlargement events of a single LD in a very brief computational time, from seconds up to few minutes. Results: The main processes regulating the interactions between LDs are here presented, and for each of them, all the needed information to re-write the computational routine are provided. More specifically, the results obtained, analyzing the fusion process between LDs, are here presented. Conclusions: Here, we would like to supply the basis to explore the dynamics of lipid storage in cells with a computational approach and to encourage the applications of numerical simulation to cell studies.